How does aquaculture activity affect phytoplankton functional groups in Gaoyou Lake, China. Issue 1 (31st December 2023) - Ge, You; Gu, Xiaohong; Mao, Zhigang; Chen, Huihui; Zeng, Qingfei; Yang, Huiting
Abstract: Aquaculture in lakes is an important human activity that could accelerate eutrophication. Its impacts on aquatic ecosystems have attracted extensive attention. This study was carried out in Gaoyou Lake, China. We investigated environmental variables and phytoplankton in areas with different aquaculture intensities over four seasons. Marked differences in diversity, biomass and phytoplankton community structure were observed across areas. The 59 phytoplankton taxa identified could be divided into 20 functional groups (PFGs), of which groups B, D, E, J, MP, P, S1, W1 and Y were dominant PFGs in different areas. Total phosphorus (TP), ratio of nitrogen and phosphorus (TN/TP) and chemical oxygen demand (CODMn ) were important driving factors for spatial differences in phytoplankton functional groups. Aquaculture altered the phytoplankton community structure, leading to a significant increase in phytoplankton biomass and diversity, especially cyanobacterial biomass. However, phytoplankton biomass and diversity could be significantly reduced and restored to natural levels after the cessation of aquaculture. This study clarified the effects of aquaculture activity on the phytoplankton community, thereby providing fundamental information for better understanding the impacts of aquaculture on lake eutrophication.